Effectiveness of Notary Deed Preparation Services for the Unfortunate Community Without Being Charged an Honorary Fee Based on the Notary Office Law - Salam, Widya Nur (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Notary is a public official, a profession that is very important to help provide legal certainty to the community, a job that was born because it was needed by the community, not a job that was created intentionally and then known by the community. By definition, a notary is a public official, but he is not an employee according to the law or civil service regulations. Notaries do not receive a salary or pension from the government, but notaries only receive an honorarium as a tribute to their services or can provide free services to those who are unable. The author researched with the aim of knowing and analyzing the services of making notarial deeds for the poor without being charged an honorarium based on the UUJN and analyzing what sanctions are for notaries who violate the honorarium provisions that have been set by the UUJN. To find out the above objectives, the author uses Empirical legal research. The theories used in this study are the Theory of Dignified Justice and the Theory of the Working of Law. Data sources are obtained through several stages, namely field research (interviews) and literature. Data analysis is qualitative and presented descriptively, namely explaining, describing, and describing according to the problems that are closely related to this study. Based on the research results, it was concluded that, first, the provision of notarial deed making services without charging an honorarium based on Article 37 No. 2 of 2014 Amendment to Law No. 30 of 2004 concerning Notary Positions is very effective and very beneficial for the underprivileged. Second, sanctions for notaries who violate the provisions of the established honorarium can be in the form of civil sanctions, administrative sanctions in the form of verbal warnings, written warnings, dismissal, honorable dismissal and dishonorable dismissal. As well as moral sanctions and ethical code sanctions for those who refuse to provide free services to the underprivileged.Keywords: Honorarium; Notary; Society.